A study on the challenges of key performance indicator (KPI) setting faced by head of department in the hotel industry / Camilia Chanda Deck - Deck, Camilia Chanda (2024)
Key performance indicators, or KPIs for short, are quantitative, measurable metrics that are used to monitor a target's progress. Key performance indicators assist businesses in assessing their advantages and disadvantages, making data-driven choices, and maximizing performance. Key performance indicators are values or measures used in the hotel industry to assess how well a certain section of hotel operations is performing, or how well the property is performing overall. They guarantee unmistakable sight into the viability and functionality of your company in the hotel industry. This study is to determine the challenges for the Head of Departments to set the key performance indicators for employees. A selected sample of Head of Departments from Penview Hotel and Convention were given questionnaire to answer by Google form. The questionnaire result determined the most challenge faced by the Head of Departments of Penview Hotel and Convention to set the Key Performance Indicators for their employees.